Copyrighting God: ownership of the sacred in American religion - Ventimiglia, Andrew (Cambridge University Press, 2019)
Spirited possessions : the sacred work of copyright law -- The angels' share : divining sacred authorship in the courtroom -- Authorship and authority in intellectual property : the copyright activism of Mary Baker Eddy -- A market in prophecy : secular law and the economy of american religious publishing -- Digital liability and the church of scientology : copyright, secrecy, and human agency online